The preliminary assessment of the selected Paleozoic deposits of the Holy Cross Mountains - MALEC, Janusz; WIĘCŁAW, Dariusz; ZBROJA, Stanisława (Geology, Geophysics and Environment, 2010)
The hydrocarbon potential of selected Paleozoic lithostratigraphic complexes of the Holy Cross Mountains was determined based on the results of Rock-Eval pyrolysis of 47 samples. For investigations only rocks in dark colours from Cambrian, Ordovician, Silurian, Carboniferous and Permian strata were selected. The Cambrian and Ordovician strata from the Łysogóry Region have poor source-rock parameters. Among the Silurian strata, the claystones of the Bardo Beds (ca. 3 wt. % TOC) are the richest in total organic carbon (TOC). The claystones of the Zaręby Formation (Carboniferous - Visean and Tournaisian) have mean TOC content ca. 2.8 wt. % and the Zechstein Limestone (Permian) ca. 1.6 wt. % TOC. In the Early Paleozoic strata marine kerogen (Type-II) is present. It dominates also in the Upper Paleozoic strata. Local inputs of the terrigenous Type-III kerogen were confirmed in the Zaręby Formation (Carboniferous). The Cambrian and Ordovician strata in the Łysogóry region are overmature. Maturity of the investigated Silurian, Carboniferous and Permian strata corresponds with the initial and middle phases of the "oil window". The NW margin of the Holy Cross Mountains, where the Paleozoic complexes rich in the organic matter are covered by the Mesozoic complex, is perspective area for hydrocarbon exploration.